The Effect Of The Contextual Teaching Learning (CTL) Learning Model On The Mathematics Learning Outcomes Of Grade III Students - Pakpahan, Saulina; Sitio, Hetdy; Sibarani, Imelda Sabrina (Jurnal Ilmu Sosial dan Humaniora, 2025)
Contextual Teaching Learning (CTL), Mathematics, Learning Results The aim of this research is to determine the effect of the Talking Stick learning model on Mathematics learning outcomes in class V students at UPTD SD Negeri 122399 Pematangsiantar. The type of research used in this research is quantitative research. The research design that will be used is an experiment, in the form of Pre- experimental Design which uses a "one group pretest-posttest design" design and the sample in this research is class students at UPTD SD Negeri 122399 Pematangsiantar, totaling 20 students. The instrument used in this research is a test. The data was tested using analysis and assisted by SPPS Version 26. The results of research hypothesis testing which had a significant influence on this research and the data that had been tested, were stated to be seen from the analysis of data obtained from the average results of the experimental class in the pretest (47,75) and posttest (82,25). Results The research obtained tcoun> ttable (12,089>1,729) with a significance level of 0.05. So it can be concluded that the Talking Stick learning model has an influence on Mathematics learning outcomes for class III students at UPTD SD Negeri 122399 Pematangsiantar.